Refractive Index, Band Gap and Oscillator Parameters of ZnO: (PNaphtholbenzenin(α)) Flims - Fadhil A. Tuma; Ghufran M. Shabeeb; Haider Abdulelah (Genius Journals, 2023)
A semiconductor ZnO with a broad band gap, cheap cost, and flexibility that can be employed in a wide range of technical and scientific applications. In order to investigate the optical quality of ZnO, the paper explains how to manufacture it utilizing a sol-gel procedure with ((P- Naphtholbenzein(α)) dye. ZnO films' optical and structural characteristics were examined. Scientists used X-ray diffraction to characterize the unique ZnO:dye (XRD). Optical and dispersion parameters were determined by measuring transmittance in the wavelength range (300-900nm). The optical band gap of ZnO thin films obtained via the sol–gel approach was (3.04 eV), while the optical band gap of ZnO:dye thin films was (2.95 eV).
Keywords: Zinc oxide; crystallite size; optical band gap